2015
DOI: 10.1002/0471140864.ps1407s80
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tyrosine Sulfation on Proteins

Abstract: Tyrosine sulfation is a post-translational modification (PTM) where a sulfate group is added to a tyrosine moiety. This PTM is responsible for strengthening interaction between proteins. One of the drawbacks of studying this PTM is the lack of an antibody that can detect all tyrosine-sulfated proteins. In addition, due to the labile nature of the tyrosine sulfate, other techniques such as mass spectrometry cannot be used to study this PTM unless special modification procedures are used. This requires considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…These molecules were separated by 79.958 Da implying a PTM of tyrosine sulfation was added in 2b. 57 Notably, there is only a slight difference between sulfation-and phosphorylationderived mass shifts, e.g. 79.9568 Da vs. 79.9663 Da (~3 ppm m/z difference for a +4 charge ion at m/z 857).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules were separated by 79.958 Da implying a PTM of tyrosine sulfation was added in 2b. 57 Notably, there is only a slight difference between sulfation-and phosphorylationderived mass shifts, e.g. 79.9568 Da vs. 79.9663 Da (~3 ppm m/z difference for a +4 charge ion at m/z 857).…”
Section: Resultsmentioning
confidence: 99%
“…We then used this genome-assisted approach to characterize and identify the two sex ganglia-specific peptides 2a at m / z 837.176 ( z = 4) and 2b at 857.166 ( z = 4). These molecules were separated by 79.958 Da implying a PTM of tyrosine sulfation was added in 2b . Notably, there is only a slight difference between sulfation- and phosphorylation-derived mass shifts, for example, 79.9568 Da versus 79.9663 Da (∼3 ppm m / z difference for a +4 charge ion at m / z 857).…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosylprotein sulfotransferase, a trans-Golgi membrane enzyme, is involved in protein tyrosine sulfation, a PTM revealed for the first time in fibrinogen [78]. Several studies demonstrated that protein tyrosine sulfation plays an important role in enhancing protein-protein interaction [79]. Tyrosine-sulfation is involved in blood coagulation, optimum rolling of leukocytes on endothelial cells, chemokine receptor ligand binding, chemokine CCR5 binding to HIV-1 gp120 and entry of virus into cells, hormone binding to receptors, and protein interactions [79].…”
Section: Sulfationmentioning
confidence: 99%
“…Several studies demonstrated that protein tyrosine sulfation plays an important role in enhancing protein-protein interaction [79]. Tyrosine-sulfation is involved in blood coagulation, optimum rolling of leukocytes on endothelial cells, chemokine receptor ligand binding, chemokine CCR5 binding to HIV-1 gp120 and entry of virus into cells, hormone binding to receptors, and protein interactions [79]. It is relevant to outline that the majority of the proteins submitted to sulfation are membrane proteins, and this makes the characterization of new sulfated proteins even more difficult.…”
Section: Sulfationmentioning
confidence: 99%
“…The first complete demonstration of this idea came through a number of studies on tyrosine sulfation. Sulfation is a ubiquitous PTM found in higher eukaryotes, whereby a sulfate group is added to tyrosine, functioning to strengthen protein–protein interactions involved in processes ranging from coagulation to chemokine signaling 16. The study of sulfation, however, is limited by organismal constraints (sulfation does not occur in the common lab microbes Escherichia coli or Saccharomyces cerevisiae ), homogeneity constraints (the enzymes responsible for sulfation are expressed only in certain parts of the cell), and sequence constraints (only specific amino acid motifs can be sulfated).…”
Section: Protein Biologymentioning
confidence: 99%